ANALISIS KINERJA KEUANGAN PERUSAHAAN INDUSTRI PULP AND PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) - Badia Purnamawanto; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The purpose of this study was to investigate the application of methods of Economic Value Added (EVA) to measure the financial performance of the pulp and paper industry 2011-2014 period. The results of this study showed that the financial performance of pulp and paper companies over the period 2011-2014. PT. Indah Kiat Pulp & Paper Tbk, PT. Toba Pulp Lestari Tbk, PT. Suparman Tbk, PT. Paper Factory Tjiwi Kimia Tbk financial performance was very bad with the acquisition value indicated a negative EVA for 4 consecutive study period (2011-2014). But only at PT. Indah Kiat Pulp & Paper Tbk, which has a fairly good financial performance only in 2011 but in the year 2012 to 2014 has decreased to have a negative EVA . From the analysis of the company's performance with the EVA method, it appears that the company's performance with the EVA method is very unfavorable in because the results of the analysis of the EVA method negative result of four pulp and paper companies.Keywords: financial performance and methods of EVA